Transient simulations in water distribution networks: TSNet python package. (November 2020) - Xing, Lu; Sela, Lina
Highlights: A new, open-source Python package is created for transient simulations in water distribution networks. TSNet enables simulating system's response to various evolving conditions including operational changes in pumps and valves, pipe bursts and background leaks as well as surge protection tanks. The developed software can be easily integrated with other applications including sensor placement, event detection, and uncertainty modeling. TSNet adds modeling capabilities of unsteady hydraulics that are currently not available in open sources software. Abstract: Modeling transient flow conditions in water distribution networks (WDNs) has shown increasing usability for various applications, including burst and leak detection, sensor placement, model calibration, and risk assessment. To facilitate the integration of transient modeling in these simulation-based applications, this work contributes a new open source Python package for Transient Simulations in water Networks (TSNet). TSNet adopts the Method of Characteristics (MOC) for solving the system of partial differential equations governing the unsteady hydraulics. It allows users to simulate various conditions including operational changes in valves and pumps, as well as background leaks and pipe bursts. In this paper, the TSNet modeling framework is presented and a case study is used to showcase its capabilities of simulating WDN responses to valve closure, pump shut-off, leaks, and bursts with and without a surge protection tank. Results show that valve closure, pump shut-off, and pipe burst can generate significant transients in the WDN, while background leaks can help damp the transients to some extent.